The microbiome structure of decomposing plant leaves in soil depends on plant species, soil pore sizes, and soil moisture content - Benucci, Gian Maria Niccolò; Toosi, Ehsan R.; Yang, Fan; Marsh, Terence L.; Bonito, Gregory M.; Kravchenko, Alexandra (Frontiers in Microbiology, 2023)
Microbial communities are known as the primary decomposers of all the carbon accumulated in the soil. However, how important soil structure and its conventional or organic management, moisture content, and how different plant species impact this process are less understood. To answer these questions, we generated soil microcosm with decomposing corn and soy leaves, as well as soil adjacent to the leaves and compared it to control samples. We then used high-throughput amplicon sequencing of the ITS and 16S rDNA region to characterize these microbiomes. Leaf microbiomes were the least diverse and the most even in terms of OTU richness and abundance compared to near and far soils, especially in their bacterial component. Microbial composition was significantly and primarily affected by niche (leaves vs. soil) but also by soil management type and plant species in the fungal microbiome while moisture content and pore sizes were more important drivers for the bacterial communities. Pore size effect was significantly dependent on moisture content but only in the organic management type. Overall, our results refine our understanding of decomposition of carbon residues in the soil, and what are the factors that influence it, which are key for environmental sustainability and for evaluating changes in ecosystem functions.